Seedling Stage Drought Response in Rice - O'Toole, J.C.; Aquino, R.S.; Alluri, K. (Wiley, 1978)
Drought‐related problems of crop establishment occur in many of the world's rainfed rice (Oryza sativa L.) growing areas. Little effort has been made to breed improved cultivars for these chronically drought‐prone areas. In this note, we report investigations on the feasibility of controlled‐environment evaluation of seedling stage drought resistance among rice cultivars. Rice cultivars were grown in a glasshouse to the three leaf stage and then placed in a growth chamber with programmed diurnal changes in light, temperature, and humidity. After a 10‐day exposure to growth chamber conditions without irrigation, the trays were moved back to the glasshouse, watered, and after 3 days the seedling survival percentage determined. A wide spectrum of seedling survival percentages was found among the 206 rice cultivars screened by this method. The technique illustrated its capability to identify well‐adapted, traditional cultivars from areas where seedling stage drought is a chronic problem. Thus the technique can identify donors of this trait for hybridization purposes and can monitor the trait through a varietal improvement process.